2014
DOI: 10.5372/1905-7415.0802.278
|View full text |Cite
|
Sign up to set email alerts
|

Improved insulin sensitivity, central systolic pressure and inflammatory indicators achieved with minor weight reduction in overweight and obese subjects given education on lifestyle modification

Abstract: Background: Obesity is a global epidemic disease; lifestyle modification is an approach in the prevention and management of obesity. Objective: We determined the effects of education on modified lifestyle intervention on arterial stiffness, metabolic and inflammatory markers. Methods: Twenty-five generally healthy overweight and obese subjects completed nine months education on modified lifestyle intervention at Hospital Universiti Sains Malaysia, Kota Bharu. Subjects were regularly counselled to increase phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Our participants were within the younger age group and their clinical indicators were of normal range, therefor further improvement would be less likely. The focus of intervention would also influence the result as other studies targeting clinical indicators with health education in dietary approach managed to result in cardiovascular risks improvement [ 57 , 58 ]. Therefore, weight loss may not necessary resulting improvement of cardiovascular risks factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants were within the younger age group and their clinical indicators were of normal range, therefor further improvement would be less likely. The focus of intervention would also influence the result as other studies targeting clinical indicators with health education in dietary approach managed to result in cardiovascular risks improvement [ 57 , 58 ]. Therefore, weight loss may not necessary resulting improvement of cardiovascular risks factors.…”
Section: Discussionmentioning
confidence: 99%
“…A few lifestyle modification studies without pharmaceutical interventional had also shown that improvement in certain metabolic and inflammatory profile among overweight and obese subjects can occur with significant weight loss. For example, a study by Ariffin et al 40 had shown that nine months education on modified lifestyle intervention (by increasing physical activity and modifying diet) improved insulin sensitivity and resistance, reduced hs-CRP. Esposito et al 39 reported that through low-energy diet and increased physical activity, there were reductions in body weight, BMI, waist circumference, CRP, fasting insulin and increment in adiponectin.…”
mentioning
confidence: 99%